Daily Living Skills in Children with Autism: The Impact of Gender, Parental Self-Efficacy, and Grandparenting - Risnawati, Erna; Rochayu, Indriyani; Shofiyah, Khoiriyah; Sa'diah, Siti; Kurnia Putri, Prahastia (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2025)
Daily Living Skills (ADLS) are essential for the independence and overall development of children. However, for children with autism, these skills often present significant challenges. This quantitative study examines the factors influencing the development of ADLS in autistic children, with a focus on gender, parental self-efficacy, and grandparent involvement. A total of 96 children with autism, aged 4 to 8 years, were recruited from therapy centers and special education schools in Indonesia. Two instruments were used for data collection: a parental self-efficacy scale adapted from Bandura's theory, and the WeeFIM Scale developed by Slomine to assess children’s ADLS performance. Pearson correlation analysis revealed a significant positive relationship between parental self-efficacy and the development of children’s ADLS, indicating that higher levels of parental confidence are associated with better daily functioning in children. Gender differences were also found, with girls outperforming boys in ADLS mastery. Interestingly, children raised in dual-caregiving environments involving grandparents demonstrated lower ADLS performance compared to those raised primarily by their parents. These findings highlight the importance of strengthening parental self-efficacy through targeted training and support programs. The study also emphasizes the influence of cultural practices, particularly the role of extended family in caregiving, which may impact children's skill development. Future research should further investigate the mechanisms through which grandparent involvement affects ADLS and explore these dynamics using longitudinal designs and cross-cultural comparisons. This study advocates for culturally responsive interventions that support both parents and extended family members in nurturing the daily living skills of children with autism.